2019
DOI: 10.3390/app9071464
|View full text |Cite
|
Sign up to set email alerts
|

A Tabu List-Based Algorithm for Capacitated Multilevel Lot-Sizing with Alternate Bills of Materials and Co-Production Environments

Abstract: The definition of lot sizes represents one of the most important decisions in production planning. Lot-sizing turns into an increasingly complex set of decisions that requires efficient solution approaches, in response to the time-consuming exact methods (LP, MIP). This paper aims to propose a Tabu list-based algorithm (TLBA) as an alternative to the Generic Materials and Operations Planning (GMOP) model. The algorithm considers a multi-level, multi-item planning structure. It is initialized using a lot-for-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…This yields solutions and predictions that often exceed their quality and are characterised by the speed of completion of tasks, and this is why, it has been utilised in this work. The principal factors of the TS algorithm are [19][20][21]:…”
Section: Tabu Search Algorithmmentioning
confidence: 99%
“…This yields solutions and predictions that often exceed their quality and are characterised by the speed of completion of tasks, and this is why, it has been utilised in this work. The principal factors of the TS algorithm are [19][20][21]:…”
Section: Tabu Search Algorithmmentioning
confidence: 99%
“…As a result, their study suggested some managerial insights to facilitate better decision-making. Other studies [27][28][29][30][31][32][33][34][35][36][37][38] investigated the influence of distinct imperfect features on production processes and their subsequent corrective actions, and a multi-item, multistage decision model (including generic materials and operations planning) on the operating policy of various supply-chain and fabrication planning, operations, and management. As few past studies have concentrated on exploring the collective and individual impact of product commonality, adjustable-rate, postponement, and rework on multi-item manufacturing decision-making, this study aims to specifically address the aforementioned subject.…”
Section: Introductionmentioning
confidence: 99%
“…Não são exploradas as possibilidades de reação aos ataques, de verificação de entrega dos pacotes ou de comunicação dos ataques aos gestores da rede. 1 Tabu-lists é um mecanismo de memória de curto prazo, que mantém um registro das últimas soluções adotadas, evitando com que o algoritmo reavalie soluções previamente consideradas e fique preso no ótimo local (ROMERO-CONRADO et al, 2019) 2 Jamming é definido como o ato de intencionalmente direcionar energia eletromagnética em direção à um sistema de comunicação para interromper ou evitar a transmissão de sinais. No contexto de RSSF, jamming é o tipo de ataque que interfere com as frequências de rádio usadas pelos nós da rede (WEI et al, 2017).…”
Section: Trabalhos Relacionadosunclassified